Pollution Permits, Imperfect Competition and Abatement Technologies - Clémence Christin; Jean-Philippe Nicolaï; Jerome Pouyet (ETH Zurich, CER-ETH - Center of Economic Research, 2013)
Under imperfect competition, the effect of a cap-and-trade system on indus- try profits depends on the type of abatement technology that is used by firms: industries that use process-integrated technologies are more affected than those using end-of-pipe abatement technologies. The interaction between environmental policy and the evolution of the market structure is then studied. In particular, a reserve of pollution permits for new entrants is justified when the industry uses a process-integrated abatement technology, while a system with a preemption right may be justified in the case of end-of-pipe abatement technology.
Keywords: L13; Q53; Q58; 330; Cap-and-trade system; imperfect competition; abatement technologies